A cross-laboratory preclinical study on the effectiveness of interleukin-1 receptor antagonist in stroke. Issue 3 (March 2016) - Maysami, Samaneh; Wong, Raymond; Pradillo, Jesus M; Denes, Adam; Dhungana, Hiramani; Malm, Tarja; Koistinaho, Jari; Orset, Cyrille; Rahman, Mahbubur; Rubio, Marina; Schwaninger, Markus; Vivien, Denis; et al.
Stroke represents a global challenge and is a leading cause of permanent disability worldwide. Despite much effort, translation of research findings to clinical benefit has not yet been successful. Failure of neuroprotection trials is considered, in part, due to the low quality of preclinical studies, low level of reproducibility across different laboratories and that stroke co-morbidities have not been fully considered in experimental models. More rigorous testing of new drug candidates in different experimental models of stroke and initiation of preclinical cross-laboratory studies have been suggested as ways to improve translation. However, to our knowledge, no drugs currently in clinical stroke trials have been investigated in preclinical cross-laboratory studies. The cytokine interleukin 1 is a key mediator of neuronal injury, and the naturally occurring interleukin 1 receptor antagonist has been reported as beneficial in experimental studies of stroke. In the present paper, we report on a preclinical cross-laboratory stroke trial designed to investigate the efficacy of interleukin 1 receptor antagonist in different research laboratories across Europe. Our results strongly support the therapeutic potential of interleukin 1 receptor antagonist in experimental stroke and provide further evidence that interleukin 1 receptor antagonist should be evaluated in more extensive clinical stroke trials.